Guyanese migration and remittances to Guyana: a case study if their potentials and challenges for Guyana's economy - CORBIN, Hisakhana Pahoona (Universidade Federal do Pará, 2019)
This mixed method case study was conducted with focus on the potentials and challenges of migration and remittances on Guyana’s economy. The study examined, described and analyzed Guyana’s major migratory flows, which continue to lead to inflows of monetary and nonmonetary remittances to Guyana. Questionnaires, interviews, focus group discussions, archival records, and observations (direct and participant) were utilized to gain an in-depth understanding of the issue under study. The study confirmed that 56% of the Guyanese population has been lost to migration. As Guyanese continue to migrate, there are greater flows the USA, Canada and the United Kingdom. The study further confirms that nonmonetary remittances accounts for approximately 13% of monetary remittances to Guyana. The study also confirms a significant dependence on remittances by households to meet their basic needs, which further confirms the vulnerability of Guyana’s economy in response to shocks on the economies of the USA, Canada and the UK. In-spite of these flows of migrants and remittances, no policy on migration and remittances has been incorporated into policies for development to unlock the potential benefits for the Guyanese economy. While dimensions of migrations such as brain-drain were and still are sometimes perceived a hindrance to development, this study confirms that migration and remittances could impact positively on Guyana’s economy if appropriate policy instruments are elaborated and integrated into a policies and comprehensive development framework for Guyana.